Butterflies (Lepidoptera: Papilionoidea) from a Fragment of Atlantic Forest in the Southern Bahia State - Vila-Verde, Gabriel; Paluch, Márlon (EntomoBrasilis, 2020)
The Atlantic Forest of southern Bahia comprises a zone of high levels of biodiversity and endemism of plants, vertebrates and insects. However, there are still several gaps on the knowledge of the local Lepidoptera diversity. The objective of this study was to conduct an inventory of butterflies in a fragment of the Atlantic Forest in Porto Seguro, Bahia, Brazil to provide information on species richness. Butterflies were sampled with insect net from March 2018 to March 2019, and November 2019 to February 2020, totaling 150 h of sampling effort. Additionally, we used Van Someren-Rydon traps for collecting frugivorous butterflies in September 2018 and February 2019 representing 1,080 trap-hours. A total of 228 butterfly species were recorded. Hesperiidae (86 spp.) and Nymphalidae (77 spp.) were the most representative families, followed by Riodinidae (32 spp.), Lycaenidae (21 spp.), Pieridae (10 spp.) and Papilionidae (2 spp.). The local butterfly fauna is composed of species found in open or disturbed forest edges, and secondary vegetation. Most of the sampled species is broadly distributed in Brazil Morpho menelaus coeruleus (Perry, 1810) (Nymphalidae), Jemadia hospita hephaestos (Plötz, 1879) (Hesperiidae) and several species of Lycaenidae and Riodinidae represents a new record for northeastern Brazil.